Anticipatory and Compensatory Postural Adjustments in Response to External Lateral Shoulder Perturbations in Subjects with Parkinson's Disease. - Alexandre Kretzer E Castro de Azevedo; Renato Claudino; Josilene Souza Conceição; Alessandra Swarowsky; Márcio José Dos Santos (PLoS ONE, 2016)
The purpose of this study was to investigate the anticipatory (APA) and compensatory (CPA) postural adjustments in individuals with Parkinson's disease (PD) during lateral instability of posture. Twenty-six subjects (13 individuals with PD and 13 healthy matched controls) were exposed to predictable lateral postural perturbations. The electromyographic (EMG) activity of the lateral muscles and the displacement of the center of pressure (COP) were recorded during four time intervals that are typical for postural adjustments, i.e., immediately before (APA1, APA2) and after (CPA1 and CPA2) the postural disturbances. The magnitude of the activity of the lateral muscles in the group with PD was lower only during the CPA time intervals and not during the anticipatory adjustments (APAs). Despite this finding, subjects with PD exhibit smaller COP excursions before and after the disturbance, probably due to lack of flexibility and proprioceptive impairments. The results of this study suggest that postural instability in subjects with PD can be partially explained by decreased postural sway, before and after perturbations, and reduced muscular activity after body disturbances. Our findings can motivate new studies to investigate therapeutic interventions that optimize the use of postural adjustment strategies in subjects with PD.